PENGARUH DUKUNGAN MANAJEMEN PUNCAK DAN PENGETAHUAN MANAJER TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA PERUSAHAAN RETAIL DI MANADO (Pada PT. Ace Hardware Tbk, PT. Informa Furnishings dan Toys Kingdom) - Pontonuwu, Teza Christy; Elim, Inggriani; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Accounting information system is very important part to improve organizational efficiency and support competitiveness by providing financial and accounting information for the company. The system can be said to be effective if the system is able to produce information that is acceptable and able to meet the expectations of information in a timely, accurate, and reliable. This study aims to examine the effect of top management support and knowledge manager on the effectiveness of accounting information systems. The population in this study is retail companies located in Manado. This study used Purposive sampling technique, obtained 42 people as respondents with questionnaire as the research instrument. This study used primary data that is the answer of the respondents tabulated and processed using SPSS software (Statistic Product and Service Solution) version 22. Data analysis was performed with multiple linear regression analysis. The result of this study showed that top management support and knowledge manager simultaneously affect the effectiveness of accounting information system. Top management support as partially has a positive effect on theÂ  effectiveness of accounting information system meanwhile knowledge manager has no effect on the effectiveness of accounting information system.Keywords: Top Management Support, Knowledge Manager , Effectiveness Of Accounting Information System